Different intra-cerebrospinal distribution of linezolid in patients with inflammatory meningitis. (September 2021) - Ichinose, Naoki; Yoshikawa, Gakushi; Fukao, Eri; Ichisawa, Mai; Takahata, Tomoaki; Enoki, Yuki; Taguchi, Kazuaki; Oda, Toshimi; Tsutsumi, Kazuo; Matsumoto, Kazuaki
Highlights: The linezolid concentration was found to be similar in the right and left lateral ventricles. The linezolid concentration in the third ventricle was higher than that in the lateral ventricles. The linezolid concentration in the cerebrospinal fluid tended to increase after removal of the drainage tube. Abstract: Linezolid has excellent antibiotic activity against gram-positive organisms and is expected to be an alternative to vancomycin for the treatment of bacterial meningitis. Accumulated evidence has shown the superior pharmacokinetic characteristics of linezolid to vancomycin, such as cerebrospinal fluid penetration. However, in the treatment of meningitis, pharmacokinetic information regarding the intra-cerebrospinal distribution of linezolid and the effects of drainage on the linezolid concentration in the cerebrospinal fluid are unclear. This report describes two patient cases, in which the linezolid concentrations in the cerebrospinal fluid were in the following order: subarachnoid space (cisternal drainage and lumbar puncture) ≥ third ventricle > lateral ventricle. In addition, the linezolid concentration in the cerebrospinal fluid, collected via lumbar puncture, tended to increase after removal of the drainage. This report is novel in presenting two cases of meningitis that showed different intra-cerebrospinal distribution of linezolid in various parts of the central nervous system and an increased linezolid concentration in the cerebrospinal fluid after removal of the drainage.